Habitando culatas : nuevos espacios públicos para Bogotá (2017)
"The Bogotá metro will bring along with the mobility system, a radical change in land use. Cars will stop circulating near the subway, turning parking lots and gas pumps into waste spaces. The project proposes to build a transitory architecture that is installed on these properties and transforms them into a public space for the city."--Tomado del Formato de Documento de Grado.